2016
DOI: 10.1637/11132-050815-reg
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age, Season, and Flowingvs. Stagnant Water Habitat on Avian Influenza Prevalence in Mute Swan (Cygnus olor) in Belgium

Abstract: Due to their probable role in the spread of Asian highly pathogenic avian influenza (HPAI) H5N1 virus, and in order to explore its implication in the low pathogenic avian influenza (LPAI) virus epidemiology, mute swans represent one particular wild bird species specifically targeted in the avian influenza (AI) surveillance elaborated in Belgium. A total of 640 individual mute swans have been sampled during a 4-yr AI surveillance program (2007-2010) to determine the AI seroprevalence and viroprevalence in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Studies of AIV seroprevalence have shown that ‘adult’ birds (typically individuals 1 or 2 years after hatch-year, depending on species) are more likely than ‘juvenile’ birds (sampled during or 1 year after hatch-year) to harbour antibodies targeted at AIV NP [2027]. Here we show that not all birds defined as seropositive for AIV by NP antibody presence have equivalent levels of protection against AIV.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Studies of AIV seroprevalence have shown that ‘adult’ birds (typically individuals 1 or 2 years after hatch-year, depending on species) are more likely than ‘juvenile’ birds (sampled during or 1 year after hatch-year) to harbour antibodies targeted at AIV NP [2027]. Here we show that not all birds defined as seropositive for AIV by NP antibody presence have equivalent levels of protection against AIV.…”
Section: Discussionmentioning
confidence: 67%
“…The prevalence of AIV in healthy wild mute swan populations is low (typically less than 3% [15,27,47,48,55]), with most infections observed in juveniles (approx. 6% prevalence) [27]. Experimental evidence in mallards ( Anas platyrhynchos ) suggests that birds are infected with approximately half of all HA types (6/11) circulating in the population within the first 2 years of life [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of LPAIV in swans and geese generally demonstrate very low prevalence of infection, often in the range of 0-3% in fresh faeces (Canada goose; [6] mute swan; [21,69] several species [70][71][72]). On the other hand, data on seroprevalence suggest that many swans and geese eventually do become exposed to LPAIV: 0-14% in Canada goose, [6,24,73] 45% in mute swan, [21] 63% in pink-footed goose Anser brachyrhynchus, [74] and >95% in Emperor goose Chen canagica.…”
Section: Avian Influenza Virus/ai/aivmentioning
confidence: 99%